PENGARUH MODAL INTELEKTUAL DAN PENGUNGKAPANNYA SERTA KOMITE AUDIT TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2020) - Rizqi Harry Ramadhan; Herry Laksito (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the impact of intellectual capital and its disclosure and also audit committee on financial performance by using return on Assets (ROA).            This research used manufacturing companies that listed in Indonesia Stock Exchange in 2018 – 2020 as a population. The sample selection method used purposive sampling. From a total population of 195 companies, 117 companies were selected. This research used a sample of 306 data. The intellectual capital measurement model used VAICTM by Pulic which consist of human capital efficiency (HCE), structural capital efficiency (SCE), and capital employed efficiency (CEE). This study used multiple linear regression to analyze the data.            The result of this study indicate that intellectual capital which consist of human capital efficiency (HCE), structural capital efficiency (SCE), and capital employed efficiency (CEE) has a positive and significant effect on return on assets (ROA). Intellectual capital disclosure also has a positive significant effect on return on assets (ROA) and for the audit committee has no significant effect on return on assets (ROA).